2004
DOI: 10.1111/j.1369-7625.2004.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Feedback from community pharmacy users on the contribution of community pharmacy to improving the public's health: a systematic review of the peer reviewed and non‐peer reviewed literature 1990–2002

Abstract: Objective To systematically review feedback from pharmacy users on their perceptions and experiences of health-related advice and services provided from community pharmacies.Methods The focus of the review was community pharmacy activities in relation to promoting health and well-being, preventing ill-health and maintaining health. Searches were conducted for peerreviewed (international) and non-peer-reviewed (UK) research. Electronic databases searched included MEDLINE, EMBASE, Cochrane Library and Internatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
163
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(185 citation statements)
references
References 3 publications
19
163
1
2
Order By: Relevance
“…Surprisingly, the preference for privacy in consultations was relatively low with only 30% preferring to talk with a pharmacist in a private room. This appears to contrast with other findings suggesting that a perceived lack of private consultation facilities in pharmacies, although increasingly unwarranted, is a barrier to using community pharmacies for health advice 3,7,8,21 . This is the first study to investigate potential advertising techniques for promoting pharmacy public health services in England.…”
Section: Discussioncontrasting
confidence: 85%
“…Surprisingly, the preference for privacy in consultations was relatively low with only 30% preferring to talk with a pharmacist in a private room. This appears to contrast with other findings suggesting that a perceived lack of private consultation facilities in pharmacies, although increasingly unwarranted, is a barrier to using community pharmacies for health advice 3,7,8,21 . This is the first study to investigate potential advertising techniques for promoting pharmacy public health services in England.…”
Section: Discussioncontrasting
confidence: 85%
“…13,20,31 The findings represent the general public's (societal) perspective, rather than the views only of service users or pharmacy customers, as is the case with many other studies 10,15,31 seeking views on pharmacy services. Data were gathered using a range of different methods to maximize the diversity of the sample.…”
Section: Strengths and Limitationsmentioning
confidence: 67%
“…30 Other factors found to reduce willingness to use pharmacy services are lack of awareness of the availability of consultation rooms, lack of awareness of services and the busyness of pharmacies. 15,19,31 One further factor raised by FDG participants is that their lifetime view of the pharmacist as an expert on medicines 31 needs to change in order to accept public health services.…”
Section: "mentioning
confidence: 99%
“…Research has recognised that the public trusts advice received from community pharmacies 5 . A review of evidence has confirmed the potential of pharmacy in the area of delivering public health initiatives, and suggests that pharmacy teams can make a positive contribution to public health 6 .…”
Section: Introductionmentioning
confidence: 97%
“…An extensive body of evidence demonstrates the improved health outcomes from community pharmacy initiatives 6,9 . However, research has indicated that although the diversifying role of community pharmacy from traditional dispensing activities to greater involvement in health improvement is largely accepted, and the importance of providing health and well-being services is understood, the role is still considered secondary to medicine related roles.…”
Section: Introductionmentioning
confidence: 99%